2005
DOI: 10.1002/pc.20130
|View full text |Cite
|
Sign up to set email alerts
|

Date palm fibers as polymeric matrix reinforcement: DPF/polyester composite properties

Abstract: Due to increased awareness on the part of end users and pressure from legislators, the composite industry has begun investigating the possibility of increasing the proportion of recycled or biodegradable composite materials. Accordingly, efforts are being deployed to find alternative reinforcement and resin systems that are environmentally friendly while providing the same performance as their synthetic counterparts. Natural fibers offer the potential to act as a reinforcing material for low to medium strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 22 publications
(25 reference statements)
3
56
0
Order By: Relevance
“…The surface morphology of DPF fibers after chemical treatment is shown in Figure 7(d) which indicates that using soda treatment cleans the fiber surface of wax and fatty substances and causes fibrillation which causes the breaking down of the composite fiber bundle into smaller fibers and therefore the tensile strength of the fibers increases as reported in [14,28]. Moreover, it is anticipated that a smooth surface will facilitate extraction of the fiber from the matrix as reported in [19]. The surface morphology of chemically treated DPF fibers shows rougher surfaces than those of other treatments as shown in Figure 7(d), which are expected to increase the amount of energy required for extracting the fibers and pulling them out from the matrix in the composites.…”
Section: Distribution Characterization Of Dpfmentioning
confidence: 85%
See 1 more Smart Citation
“…The surface morphology of DPF fibers after chemical treatment is shown in Figure 7(d) which indicates that using soda treatment cleans the fiber surface of wax and fatty substances and causes fibrillation which causes the breaking down of the composite fiber bundle into smaller fibers and therefore the tensile strength of the fibers increases as reported in [14,28]. Moreover, it is anticipated that a smooth surface will facilitate extraction of the fiber from the matrix as reported in [19]. The surface morphology of chemically treated DPF fibers shows rougher surfaces than those of other treatments as shown in Figure 7(d), which are expected to increase the amount of energy required for extracting the fibers and pulling them out from the matrix in the composites.…”
Section: Distribution Characterization Of Dpfmentioning
confidence: 85%
“…The possibility of using DPF reinforcement in composite manufacturing will help in opening new markets in Arab countries like UAE and Egypt for what is normally considered waste in low value products. The use of DPF as reinforcement in polymeric materials has been reported in few studies [16][17][18][19]. Using different physical treatment methods such as corona discharge and plasma and chemical surface treatment methods such as alkali, acetylation, and bleaching has direct effect on the changes in the surface structure of the natural fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Application of plant fibres as one of the component in polymeric materials such as reinforcement in composites have attracted greater attention due to their added advantages. Natural fibres and its composites is environment friendly as these are derived from renewable sources, and at the end of life cycle either they can be composed or calorific value can be recovered [7,8]. Compared to the natural cellulosic fibres, glass fibres have been prominently used in composites industry, as no viable technological options were available.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of DP trees in the world is approximately 120 million, cultivated on an area of 800000 ha distributed in 30 countries (Al-Kaabi et al 2005;El-Juhany 2010). The analysis of the regional distribution (Table 3) indicated that approximately 60 million DP trees are found in Asia (e.g.…”
Section: Date Palm As An Emerging Biomaterialsmentioning
confidence: 99%